Improving natural rubber latex film softening due to oil - Ruhida A R; Amir-Hashim M Y (Journal of Rubber Research, 2012)
Natural rubber latex (NRL) gloves are generally accepted for thie superior mechanical properties compared to synthetic gloves in many applications. However, their tolerance to polar solvents and oils is relatively poor. This study demonstrated improvement in tolerance of NR towards oils by introducing more crosslinks in NRL gloves. This was done by increasing sulphur content in the NRL latex mixture from which gloves were prepared. Evidence of better tolerance can be deduced from the much reduced mass uptake of oil into highly crosslinked NRL films and the lower diffusion rate of oil in the NRL films. The mass uptake of oil in NRL films can also be reduced by blending nitrile latex (XNBR) with NRL latex.
Source Year: 2012
Keywords: Cooking oil; Crosslink concentration; Swelling resistance; Tensile strength; XNBR